2007
DOI: 10.1016/j.drugalcdep.2007.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent and simultaneous drug and alcohol use: Results of the 2000 National Alcohol Survey

Abstract: This study estimates the prevalence, assesses predictors and evaluates factors associated with concurrent and simultaneous use of drugs and alcohol in the United States population. Using data from the 2000 National Alcohol Survey (n=7612), respondents were asked if they used specific drugs in the last 12 months. Current drinkers who reported using each type of drug were asked if they used alcohol and the drug at the same time. Approximately 10% reported using marijuana in the last 12 months (concurrent use); 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
251
6
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(288 citation statements)
references
References 32 publications
22
251
6
6
Order By: Relevance
“…As the night passes, students reported more frequent use of cocaine, ecstasy, and LSD. Multiple drug use, as found in the present study, has been reported for the population, in particular for the young adults (Furr-Holden et al, 2006;Midanik et al, 2007), which leads to an increased effect on psychomotor performance, as well as an increase in traffic accident risk (Laumon et al, 2005;Ramaekers et al, 2004Ramaekers et al, , 2006Richer and Bergeron, 2009). It should be mentioned that, in the present study, no information was recorded regarding exposure in terms of kilometres driven.…”
Section: Discussionsupporting
confidence: 75%
“…As the night passes, students reported more frequent use of cocaine, ecstasy, and LSD. Multiple drug use, as found in the present study, has been reported for the population, in particular for the young adults (Furr-Holden et al, 2006;Midanik et al, 2007), which leads to an increased effect on psychomotor performance, as well as an increase in traffic accident risk (Laumon et al, 2005;Ramaekers et al, 2004Ramaekers et al, , 2006Richer and Bergeron, 2009). It should be mentioned that, in the present study, no information was recorded regarding exposure in terms of kilometres driven.…”
Section: Discussionsupporting
confidence: 75%
“…This phenomenon has been studied in terms of marijuana and the concurrent use of other substances such as alcohol (Blows et al, 2005;Penning et al, 2010;Scherer et al, 2013b), cocaine (Higgins et al, 2007;Lindsay et al, 2009;Scherer et al, 2013a), and opioids (Subramaniam et al, 2010), which could potentially compound detrimental effects (Midanik et al, 2007). This is of particular concern when examining everyday activities such as driving.…”
Section: Marijuana and Other Substance Use Among Motormentioning
confidence: 99%
“…Among the more serious types of substance use, poly-substance use (i.e., the use of different substances on the same or different occasions- Toumbourou and Catalano, 2005), is particularly important to consider. Adolescent poly-substance use is associated with a number of problematic outcomes, such as adverse psychological and social consequences, particularly for girls (Lex, 1995;Overman et al, 2004), increased delinquent acts for boys (Mason and Windle, 2002), an increased likelihood of developing substance abuse and other mental health problems in adulthood (Newcomb and Felix-Ortiz, 1992;Toumbourou and Catalano, 2005), lower levels of adolescent achievement motivation and adult job-related problems (Mohler-Kuo et al, 2003;Stein et al, 1993), accidental death due to drug overdose (Coffin et al, 2003), suicide (Midanik et al, 2007), high-risk sexual behaviors (Midanik et al, 2007), and substance-related accidents in adulthood .…”
Section: Introductionmentioning
confidence: 99%